Factors affecting customer satisfaction of mobile banking in Nepalese commercial banks - Bohara, Yugal (Nepalese Journal of Management, 2024)
This study investigates the factors affecting customer satisfaction of mobile banking in Nepalese commercial banks. Customer satisfaction is selected as dependent variable. The independent variables are service quality, system availability, security, ease to use and website features. The primary source of data is used to assess the opinions of the respondents regarding mobile banking and level of customer satisfaction in Nepalese commercial banks. The study is based on primary data of 15 Nepalese commercial bank, leading to a total of 120 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of service quality, system availability, security, ease to use and website features on customer satisfaction in the context of Nepalese commercial banks. The study showed that service quality has a positive impact on customer satisfaction. It indicates that better the quality of service, higher would be the customer satisfaction. Similarly, the result showed that system availability has a positive impact on customer satisfaction. It indicates that higher the availability of system, higher would be the customer satisfaction. Likewise, security has a positive impact on customer satisfaction. It indicates that higher the security, higher would be customer satisfaction. The result also showed that ease to use has a positive impact on customer satisfaction. It indicates that user friendly system leads to higher customer satisfaction. Similarly, website features has a positive impact on customer satisfaction. It indicates that better the website features, higher would be the customer satisfaction.